Fatigue fracture mechanism of Ni-base superalloy GH4065A at elevated temperatures - LI Linhan; ZHANG Ji; ZHANG Wenyun; TIAN Qiang; QIN Heyong; ZHANG Beijiang (Cailiao gongcheng)
GH4065A is a newly developed high-performance cast-wrought Ni-base superalloy with ultra-low C and N content used for advanced turbine engine disc. In this study， the alloy’s inclusions of the alloy are characterized and statistically analyzed. To investigate the fatigue fracture mechanism， strain-controlled fatigue tests are conducted at 400 ℃ and 650 ℃ on the fine-grained and coarse-grained samples respectively. The results show that the alloy’s inclusions of the alloy are mainly nitrides. For the fine-grained samples， discrete nitride particles and clustered nitrides both with a critical size larger than the average grain size are responsible for the fatigue crack initiation. When subjected to high-level strains （≥0.9%）， fatigue failure primarily originates from surface nitrides， with rare occurrences of boride and oxide initiation. Surface crack induced by Al2O3， rather than boride or MgSiO3， is found to significantly reduce the fatigue life. Higher fatigue temperature results in reduced life cycles. When under lower levels of strain， however， subsurface/internal nitride-facet initiations dominate and fatigue life is prolonged by the elevated temperature. In the coarse-grained samples， fatigue failures at 400 ℃ are found to be initiated by quasi-cleavage cracking mechanism. Due to the increased grain size， the inclusion-induced crack initiation is suppressed while slip-induced cleavage cracking mechanism becomes predominant.